Causal Factors Affecting the Decision to Receive Coronavirus (COVID-19) Booster Dose of People at Kamphaeng Saen Hospital - Yuangngoen, Pawit (Journal of Preventive Medicine Association of Thailand, 2023)
Objective: The objectives are to study; 1) the level of decision to vaccinate COVID-19 booster dose, 2) the level of factors of affecting the decision to vaccinate COVID-19 booster dose, and 3) causal factors of affecting the decision to vaccinate COVID-19 booster dose. Methods: This research is a cross-sectional study of sample group was 400 people who receiving services at Kamphaeng Saen Hospital, the purposive sampling was applied. The five research tools were the characteristic questionnaire. The decision to vaccinate COVID-19 booster dose questionnaire, the self-efficacy perception of COVID-19 prevention questionnaire, the perception of COVID-19 severity questionnaire and, the expectation of the efficiencies of COVID19 booster dose. The frequency, percentage, mean, standard deviation, coefficient of variation and influence analysis or path analysis were analyzed data. Results: The study findings revealed as follows: 1) the level of decision to vaccinate COVID-19 booster dose of patients at Kamphaeng Saen Hospital were high. 2) The level of factors of affecting the decision to vaccinate COVID-19 booster dose of patients at Kamphaeng Saen Hospital showed that 2.1) the level of self-efficacy perception of COVID-19 prevention were highest, 2.2) The level of perception of COVID-19 severity were highest and 2.3) the level of expectation of the efficiencies of COVID19 booster dose were highest. 3) The factors affecting the decision to receive COVID-19 booster dose of people at Kamphaeng Saen Hospital were influenced by the expectation of the efficiencies of COVID19 booster dose and the perception of COVID-19 severity. These two variables could explain the variance of decision to vaccinate COVID-19 booster dose of patients at Kamphaeng Saen Hospital at 47.00% which was statistically significant at .01. In addition, decision to vaccinate COVID-19 booster dose of patients at Kamphaeng Saen Hospital was affected indirectly from the self-efficacy perception of COVID-19 prevention, perception of COVID-19 severity through the expectation of the efficiencies of COVID19 booster dose. Conclusion: Self-efficacy perception of COVID-19 severity expectation of the efficiencies of COVID19 booster dose affecting the decision to receive coronavirus (COVID-19) booster dose of people at Kamphaeng Saen Hospital.